Monitoring terrestrial rewilding with environmental DNA metabarcoding: a systematic review of current trends and recommendations - Cowgill, Clare; Gilbert, James D. J.; Convery, Ian; Lawson Handley, Lori (Frontiers in Conservation Science, 2025)
IntroductionRewilding, the facilitation of self-sustaining and resilient ecosystems by restoring natural processes, is an increasingly popular conservation approach and potential solution to the biodiversity and climate crises. Outcomes of rewilding can be unpredictable, and monitoring is essential to determine whether ecosystems are recovering. Metabarcoding, particularly of environmental DNA (eDNA), is revolutionizing biodiversity monitoring and could play an important role in understanding the impacts of rewilding but has mostly been applied within aquatic systems.MethodsThis systematic review focuses on the applications of eDNA metabarcoding in terrestrial monitoring, with additional insights from metabarcoding of bulk and ingested DNA. We examine publication trends, choice of sampling substrate and focal taxa, and investigate how well metabarcoding performs compared to other monitoring methods (e.g. camera trapping).ResultsTerrestrial ecosystems represented a small proportion of total papers, with forests the most studied system, soil and water the most popular substrates, and vertebrates the most targeted taxa. Most studies focused on measuring species richness, and few included analyzes of functional diversity. Greater species richness was found when using multiple substrates, but few studies took this approach. Metabarcoding did not consistently outperform other methods in terms of the number of vertebrate taxa detected, and this was likely influenced by choice of marker, sampling substrate and habitat.DiscussionOur findings indicate that metabarcoding, particularly of eDNA, has the potential to play a key role in the monitoring of terrestrial rewilding, but that further ground- truthing is needed to establish the most appropriate sampling and experimental pipelines for the target taxa and terrestrial system of interest.Systematic Review Registrationhttps://osf.io/38w9q/?view_only=47fdab224a7a43d298eccbe578f1fcf0, identifier 38w9q.